De la question des apprentissages formels et informels dans la mobilité académique courte - Marie Françoise Pungier (Recherches en didactique des langues et des cultures)
This study focuses on how the various actors involved in a short stay abroad deal with the possibilities of learning in formal and informal situations that exist in all possible spaces and temporalities. First, we try to identify the general configuration of a short academic mobility stay. We note that formal learning takes place in parallel with informal learning. Secondly, we look at the question of their assessment based on the case of short stays in a Japanese university. These examples suggest a default assessment of learning during mobility. In the third part, we recommend rethinking the configuration of short mobility as an experience constructed by the interrelations of the actors, providing the basis for the assessment of all mobility earning without distinction of their nature.